The cross-sectional association between state-level public health funding per capita and physical health among adults in the United States. - Stephen Hunter; Sze Y Liu; Daniel M Cook; Kia L Davis; Brendan T Smith; Roman Pabayo (PLoS ONE)
Objectives This study examined the association between state-level public health funding per capita and the odds of poor physical health. Study design Cross-sectional. Methods Data from the 2018 Behavioral Risk Factor Surveillance System (BRFSS) were used. Participants' self-reported physical health was reported using the CDC Healthy Days Core Module. State-level public health funding per capita was obtained from the State Health Access Data Assistance Center website. Multilevel logistic regression was used to adjust for self-reported individual-level characteristics and state-level characteristics from the 2018 American Community Survey. We also tested whether household income or education attainment moderated any observed associations. Results A one SD increase in state-level public health funding per capita was not associated with the odds ≥  14 days of poor physical health (OR = 0.96, 95% CI: 0.90, 1.01). However, heterogeneity across household income was observed. Greater public health funding per capita was associated with lower predicted probabilities of reporting ≥  14 days of poor physical health among respondents from low household income backgrounds ( <$35,000 USD) compared to participants with high household incomes (>$75,000 USD). No associations were observed among those with moderate ($35,000 - $70,000 USD) household incomes. A similar finding was observed among participants with less than high school education when compared to participants with post-secondary education. Conclusion Greater state-level public health funding per capita appears to have a protective association against reporting ≥  14 days of poor physical health in individuals with lower household incomes and may be helpful in reducing health inequities. Future research is needed to determine whether this association is causal.